Autologous Chondrocyte Transplantation in Femoroacetabular Impingement Syndrome: Growth and Redifferentiation Potential of Chondrocytes Harvested from the Femur in Cam-Type Deformities. (July 2021) - Wilken, Frauke; Slotta-Huspenina, Julia; Laux, Florian; Blanke, Fabian; Schauwecker, Johannes; Vogt, Stephan; Gollwitzer, Hans
Objective: Cam-type femoroacetabular impingement (FAI) syndrome is one of the most frequent reasons for cartilage damage in the hip. Autologous chondrocyte transplantation has proven high success rates in the treatment of focal chondral defects; however, harvesting of chondrocytes in the hip has been reported but not specifically from the region of femoral cam lesions. Therefore, the goal of this study was to analyze the growth and redifferentiation potential of cartilage samples harvested from the cam deformities in patients with FAI. Design: Cartilage samples were gained from 15 patients with cam-type FAI undergoing arthroscopic femoral cam resection. Healthy (hyaline cartilage of the hip and knee joint, n = 12) and arthritic control groups (degenerative changes in cartilage of the hip joint, n = 8) were also analyzed. Chondrocytes were initially cultured under monolayer, and subsequently under pellet conditions. A comparative representation of the groups was performed by Mankin score classification, immunohistochemistry (IHC) (Col1, Col2, aggrecan), and quantitative reverse transcription–polymerase chain reaction (qRT-PCR) (Col1, Col2, Col10, Sox9, RunX2). Results: Mankin score of FAI-samples (4.1±3.1, Range 0-10) showed a wide variation but was significant lower ( P = 0.0244) when compared with the arthritic control (7.5 ± 2.7, range 4-12). IHC showed an increased deposition of Col2 ( P = 0.0002) and aggrecan ( P = 0.0261) after pellet culture compared with deposition after monolayer culture in all groups. In qRT-PCR, FAI samples showed after pellet culture increased Col2 ( P = 0.0050) and Col10 expression ( P = 0.0006) and also Mankin score correlated increasing gene-expression of Col10 ( r = 0.8108, P = 0.0341) and RunX2 ( r = 0.8829, P = 0.123). Conclusions: Cartilage samples of patients with cam-type FAI showed sufficient but heterogeneous composition relating to histological quality and chondrogenic potential. However, harvesting of chondrocytes from the cam lesion might be a valid option especially if a cartilage lesion is noted in a diagnostic arthroscopy and individual preexisting stage of cartilage degeneration and appropriate pellet-culturing conditions are considered.